Gene–environment interplay in depressive symptoms: moderation by age, sex, and physical illness. Issue 10 (16th February 2017) - Petkus, A. J.; Beam, C. R.; Johnson, W.; Kaprio, J.; Korhonen, T.; McGue, M.; Neiderhiser, J. M.; Pedersen, N. L.; Reynolds, C. A.; Gatz, M.
Abstract : Background: Numerous factors influence late-life depressive symptoms in adults, many not thoroughly characterized. We addressed whether genetic and environmental influences on depressive symptoms differed by age, sex, and physical illness. Method: The analysis sample included 24 436 twins aged 40–90 years drawn from the Interplay of Genes and Environment across Multiple Studies (IGEMS) Consortium. Biometric analyses tested age, sex, and physical illness moderation of genetic and environmental variance in depressive symptoms. Results: Women reported greater depressive symptoms than men. After age 60, there was an accelerating increase in depressive symptom scores with age, but this did not appreciably affect genetic and environmental variances. Overlap in genetic influences between physical illness and depressive symptoms was greater in men than in women. Additionally, in men extent of overlap was greater with worse physical illness (the genetic correlation ranged from near 0.00 for the least physical illness to nearly 0.60 with physical illness 2s.d. above the mean). For men and women, the same environmental factors that influenced depressive symptoms also influenced physical illness. Conclusions: Findings suggested that genetic factors play a larger part in the association between depressive symptoms and physical illness for men than for women. For both sexes, across all ages, physical illness may similarly trigger social and health limitations that contribute to depressive symptoms.